SENI KOLOPETONG TASIKMALAYA: RELASI ARAK-ARAKAN, PENCAK SILAT DAN SISINGAAN - Dannurie, Wily (Paraguna, 2023)
Kolopetong art is an art originating from the Cisayong Tasikmalaya area. This art basically combines the arts of Penca and Sisingaan. Kolopetong as an art that not many researchers have written and described sparked the author to make it the purpose of phenomenological studies. The choice is based on the fact that phenomenology is generally known as an approach that sees an event speaking as it is. Kolopetong, as a newly recognized art form in Tasikmalaya, is closely related to the tradition of processions. In the current context, processions are generally synonymous with the independence ceremony of the Republic of Indonesia, or other events that are massive, large, related to the anniversary of the city. Kolopetong art as a new entity in Tasikmalaya shows that cultural creativity derived from existing traditional arts gives rise to new entertainment for the community.